Plasticity of bone marrow-derived cell differentiation depending on microenvironments in the skin - Okano, Junko; Nakagawa, Takahiko; Kojima, Hideto (Frontiers in Physiology, 2024)
Bone marrow-derived cells (BMDCs) are heterogeneous populations in which not only pluripotent stem cells, namely, hematopoietic stem cells (HSCs), mesenchymal stem cells (MSC) but also endothelial progenitor cells (EPC) are involved. BMDCs contribute to the maintenance of homeostasis and recovery from disrupted homeostasis as the immune, endocrine, and nervous systems.The skin is the largest organ in which various tissues, such as the epidermis, dermis, skin appendages (i.e., hair follicles), fats, muscles, and vessels, are tightly and systematically packed. It functions as a physical barrier to block the invasion of harmful substances and pathogenic microorganisms and properly regulate water evaporation. The skin is exposed to injuries from external stimuli because it is the outermost layer and owing to its specificity.Recovery from physical injuries and DNA mutations occurs constantly in the skin, but medical treatments are required for impaired wound healing. Recently, conservative treatments utilizing scaffolds have attracted attention as alternatives to surgical therapy, which is highly invasive. Against this background, numerous scaffolds are available in a clinical setting, although they have not surpassed surgery because of their distinct disadvantages.Here, we discuss the plasticity of BMDCs in the skin to maintain homeostasis, in addition to their critical roles on recovery from disrupted homeostasis. We also share our perspective on how scaffolds can be developed to establish scaffolds beyond surgery to regenerate skin structure during wound healing by maximally utilizing the plasticity of BMDCs.